Optimalisasi Penggunaan Laboratorium IPS/PKn Dalam Upaya Peningkatan Kualitas Pembelajaran Mahasiswa PGSD VI Bone UNM - Andi Sri Wahyuni Mumang; Sitti Jauhar; Muhammad Awal Nur; Nursalim; Andika Marsuki (Jurnal Abdi Masyarakat Pendidikan, 2026)
This community service is motivated by the low utilization of the Social Studies/Civics Laboratory as a learning support facility in the Elementary School Teacher Education Program VI Bone at Makassar State University. The problems identified include the minimal use of the laboratory in lectures, students' limited understanding of the laboratory's functions, and the suboptimal condition of the facilities and infrastructure. This community service aims to optimize the use of the Social Studies and Civics Laboratory in an effort to improve the quality of student learning. The method employed is an educational participatory approach, consisting of three stages: observation, planning, and implementation. The results of the activity showed students' enthusiasm for using the laboratory; moreover, students were able to understand the functions and usage of the laboratory. Optimization of laboratory use provides a more concrete and meaningful learning experience, thereby having a positive impact on the quality of student learning. This activity is expected to encourage the sustainable and integrated use of laboratories in the lecture process